2013
DOI: 10.1111/cea.12218
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 and MDA5 signalling, although not expression, is impaired in asthmatic epithelial cells in response to rhinovirus infection.

Abstract: Impaired antiviral responses in asthmatic pBECs are not due to deficient expression of PRRs; MDA5 and TLR3, but an inability to later activate types I and III interferon immune responses to RV infection, potentially increasing susceptibility to the effects of RV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 29 publications
3
62
0
Order By: Relevance
“…Eosinophilic asthmatics also expressed lower levels of innate IFNs in addition to TLR7, a difference that was not observed for expression of TLR3, retinoic acid-inducible gene I or melanoma differentiation-associated gene 5. 27 These results are congruent with a recent study that mapped TLR7 expression in the airways of severe asthmatics. 28 Our results suggest a reciprocal regulation between IL-5-induced eosinophilia and TLR7 expression that affects antiviral IFN responses to RV (summary illustrated in figure 5).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Eosinophilic asthmatics also expressed lower levels of innate IFNs in addition to TLR7, a difference that was not observed for expression of TLR3, retinoic acid-inducible gene I or melanoma differentiation-associated gene 5. 27 These results are congruent with a recent study that mapped TLR7 expression in the airways of severe asthmatics. 28 Our results suggest a reciprocal regulation between IL-5-induced eosinophilia and TLR7 expression that affects antiviral IFN responses to RV (summary illustrated in figure 5).…”
Section: Discussionsupporting
confidence: 91%
“…This finding was of clinical relevance because we observed reduced TLR7 expression in endobronchial biopsies from asthmatic patients with eosinophilic inflammatory profiles. Eosinophilic asthmatics also expressed lower levels of innate IFNs in addition to TLR7, a difference that was not observed for expression of TLR3, retinoic acid-inducible gene I or melanoma differentiation-associated gene 5 27. These results are congruent with a recent study that mapped TLR7 expression in the airways of severe asthmatics 28…”
Section: Discussionsupporting
confidence: 87%
“…Activation of TLR3 then leads to the induction of other subsequent pattern recognition receptors such as retinoic acid inducible protein I (RIG-I) and melanoma differentiation associated gene 5 (MDA5) (Wang et al, 2009). However, the exact subsequent inflammatory effects of TLR3-pathways stimulated by HRV are not well understood, and inflammation may result from an abnormal downstream signaling defect (Parsons et al, 2014). There have also been alternative sensing mechanisms proposed such as TLR7 and TLR8, though the data remain inconclusive as to their exact role in initiating an immune response to HRV (Morris et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, there is considerable evidence of decreased production of interferon (IFN)-α2, IFN-β1 and IFN-λ2/3 by airway epithelial cells (AEC) from asthmatics, in response to stimulation with double-stranded RNA (dsRNA) or with RV [7-11]. This has been related to impaired toll-like receptor (TLR) and helicase signalling [12]. It has also been suggested that similar impairment is demonstrable in atopic individuals even without asthma [13], although this has not been confirmed.…”
Section: Introductionmentioning
confidence: 99%